Principal Leadership and Educational Quality Management: A Case Study in Indonesian Elementary School - Yanti, Ni Nyoman Anis Kristina; Rizal, Rizal; Pahriadi, Pahriadi; Aqil, Muhammad; Wilade, Surahman; Lapasere, Sisriawan (Journal of Innovation and Research in Primary Education, 2026)
Effective principal leadership is crucial for implementing educational quality management in elementary schools, yet empirical evidence from Indonesian contexts remains limited. This study examined how principal leadership practices contribute to successful quality management implementation at SDN 5 Tolai, Central Sulawesi. A qualitative descriptive case study was employed, involving nine participants comprising one principal and eight teachers. Data were collected through semi-structured interviews, document analysis, and structured questionnaires using a five-point Likert scale. Qualitative data were analyzed using Miles et al.'s interactive model, while quantitative data employed percentage descriptive analysis. The principal demonstrated highly effective leadership with 97.5% overall effectiveness rating across transformational influence, participatory decision-making, strategic teacher empowerment, quality culture development, and continuous improvement mechanisms. Five interconnected themes emerged: transformational and inspirational motivation through personal example, participatory governance balancing consultation with administrative efficiency, competency-based delegation enhancing teacher confidence, institutionalized integrity values fostering transparency, and monthly reflection sessions supporting systematic evaluation. Observation confirmed 93.75% quality management implementation, though facility optimization gaps revealed resource constraints beyond leadership control. Effective principal leadership significantly contributes to sustainable educational quality management through synergistic integration of transformational leadership behaviors and Total Quality Management principles, demonstrating that relational trust and systematic processes outweigh material resources in driving quality improvement.